Evaluation of the difficulty index of questions from the general admission test 2014-II at San Marcos National University. The case of a linear associations grouping careers - Orrego E., César (2014)
This descriptive corelational work states the following: First, the questions customary to applicants for the Humanities, Social Sciencies and Economics of Business General Admission Test 2014 - II vary in scale from Extremely Easy. In general, most of the questions qualify as Hard, Medium and Easy.